2020
DOI: 10.1136/bmjoq-2020-000913
|View full text |Cite|
|
Sign up to set email alerts
|

Promoting hot debriefing in an emergency department

Abstract: IntroductionDebriefing is a process of communication that takes place between a team following a clinical case. Debriefing facilitates discussion of individual and team level performance and identifies points of excellence as well as potential errors made. This helps to develop plans to improve subsequent performance. While the American Heart Association and the UK Resuscitation Council recommend debriefing following every cardiac arrest attended by a healthcare professional, it has not become part of everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…During a period of promotion for ‘hot debriefs’ following cardiac arrest incidents in an Irish emergency department, the authors found that staff appreciated debriefing as a helpful tool for quality improvement and quality of patient care. However, it was noted that it was difficult to maintain high and consistent participation rates due to unawareness and/or forgetfulness [70] . A survey of US emergency medicine training program leaders found that barriers to debriefing of paediatric critical events included timing and scheduling of the clinical debrief [71] .…”
Section: Discussionmentioning
confidence: 99%
“…During a period of promotion for ‘hot debriefs’ following cardiac arrest incidents in an Irish emergency department, the authors found that staff appreciated debriefing as a helpful tool for quality improvement and quality of patient care. However, it was noted that it was difficult to maintain high and consistent participation rates due to unawareness and/or forgetfulness [70] . A survey of US emergency medicine training program leaders found that barriers to debriefing of paediatric critical events included timing and scheduling of the clinical debrief [71] .…”
Section: Discussionmentioning
confidence: 99%
“…Debriefing can be utilised after any situation where it is expected to be of value for participants. It allows for discussion of individuals' and team performance during a traumatic event, promoting teams to analyse both clinical and communications performance, develop processes to improve subsequent experiences and mitigate the risk of future adverse outcomes 2 . Originating in the military, 3 it has also been used by other departments exposed to high risk events, including police.…”
Section: Why When and Who Should We Debrief?mentioning
confidence: 99%
“…The concept of the ‘hot’ debrief is one which takes place immediately after a significant incident, as compared with ‘warm’ (minutes to hours later), or ‘cold’ debriefs, which may take place days to weeks after an event 4 . Where a hot debrief can provide immediate team feedback between those involved in a critical event, it can be subject to the ‘hot’ emotional overlay of a traumatic resuscitation – these reactions can, however, be effectively utilised to identify processes that can be improved on, and in a timely fashion 2 . Hot debriefs also provide an opportunity for a ‘time‐out’ from the incessant clinical load of a busy shift and represent an important moment to consider the psychological needs of the individual and the team.…”
Section: Hot Versus Cold Debriefsmentioning
confidence: 99%
See 2 more Smart Citations